Reproductive Cycle and Periodicity of In Situ and Aquarium Female Sand Tiger Sharks Carcharias taurus from the Western North Atlantic - Wyffels, Jennifer T.; George, Robert; Christiansen, Emily F.; Clauss, Tonya M.; Newton, Alisa L.; Hyatt, Michael W.; Buckner, Chris; LePage, Véronique; Latson, F. Ed; Penfold, Linda M. (Frontiers in Marine Science, 2022)
Fundamental characteristics of the reproductive biology of female sand tiger sharks Carcharias taurus are needed to understand the periodicity, seasonality and environmental factors essential for reproduction in this iconic species. Animals in managed care, such as aquariums, provide the unique opportunity for longitudinal study in contrast to in situ sharks that are examined opportunistically, and at a single point in time. Additionally, comparison of reproductive observations from successfully reproducing in situ sharks and aquarium sharks may help elucidate reasons for lack of reproduction among aquarium sharks and aid the development of assisted reproductive techniques for managed populations. Reproductive status of in situ and aquarium female sharks was assessed using ultrasonography and plasma hormone (17β-estradiol, testosterone, and progesterone) monitoring. The reproductive cycle was divided into eight stages based on ovarian activity and uterine contents. In situ sharks were sampled from Delaware Bay (n = 29), North Carolina (n = 39) and South Carolina (n = 11) during April-November from 2015–2020. Nineteen aquarium females from five aquaria were examined longitudinally for two or more consecutive years. Reproductive regionalization was observed among in situ females with the majority (83%) of North Carolina females in an active state of reproduction and all Delaware females in a resting reproductive state. All aquarium females had a pattern of reproductive cycling that was consistent with alternating years of activity and rest with confirmed biennial (n = 7) or triennial (n = 3) reproductive cycles with spring seasonality. In contrast to in situ females, aquarium females often retained uterine eggs for 9-20 months after ovulation in the absence of a developing embryo(s). Pre-ovulatory aquarium females had significantly higher concentrations of 17β-estradiol, testosterone and progesterone than other reproductive stages. For females in the ovulatory stage, in situ females had higher testosterone than aquarium females. Endocrine differences between successfully reproducing in situ females and aquarium females likely contribute to the limited reproductive success observed for this species in managed care and may be a reflection of diminished seasonal cues and environmental differences.